Europejska filozofia praw człowieka a konstytucyjna formuła obowiązków człowieka i obywatela - Liżewski, Bartosz (Filozofia Publiczna i Edukacja Demokratyczna, 2018)
This article is devoted to the problem of the obligations of a human and citizen in the Polish constitution. This matter is shown from the philosophy and legal point of you. The aim of the article is to show what influence the philosophy of human rights had on regulating the obligations of human and citizen in the European and Polish law. The main idea is, that the constructions of the provisions in the Polish constitution is the reflection of the European philosophy on human rights. This philosophy is based on the individualization and personalization on the human. Therefore the freedoms and rights are underlined and its obligations are limited. The provisions on the Constitution of the Republic of Poland which concern the obligations agree this philosophy. In the opinion of the author of this article these solutions are not good. All the provisions regulating the obligations of a human and citizen can be called the obligations towards the country. They include, loyalty to the Republic of Poland, observing the Polish law, paying taxis, defending the country and protecting the environment. The authors of the constitution omitted the obligations towards the family and local communities.